High frequency and microwave engineering - Da Silva, Ed
Provides a comprehensive course in radio and microwave engineering. This title includes a CD-ROM, containing the CAD package PUFF 2.1 for construction and evaluation of circuits, and a comprehensive section on practical aspects of design. It covers transmission lines, scattering parameters, couplers, amplifiers, oscillators and phase-locked loops.